Clinical cosmeceutical repurposing of melatonin in androgenic alopecia using nanostructured lipid carriers prepared with antioxidant oils. (3rd October 2018) - Hatem, Shymaa; Nasr, Maha; Moftah, Noha H; Ragai, Maha H; Geneidi, Ahmed S; Elkheshen, Seham A
ABSTRACT: Background : The present work aims to formulate nanostructured lipid carriers (NLCs) exhibiting high skin deposition and high inherent antioxidant potential to repurpose the use of melatonin hormone and some antioxidant oils in the treatment of androgenic alopecia (AGA). Research design and methods : NLCs were characterized for their size, charge, drug entrapment, anti-oxidant potential, physical stability, in vitro release, surface morphology, and ex-vivo skin deposition. Their merits were clinically tested on patients suffering from AGA by calculating the degree of improvement, conduction of hair pull test, histometric assessment, and dermoscopic evaluation. Results : Results revealed that melatonin NLCs showed nanometer size, negatively charged surface, high entrapment efficiency, and high anti-oxidant potential, in addition to sustained release for 6 h. Furthermore, NLCs displayed good storage stability and they were able to increase the skin deposition of melatonin 4.5-folds in stratum corneum, 7-folds in epidermis, and 6.8-folds in the dermis compared to melatonin solution. Melatonin NLCs displayed more clinically desirable results compared to the melatonin solution in AGA patients, manifested by increased hair density and thickness and decreased hair loss. Conclusions : The aforementioned system was shown to be a very promising treatment modality for AGA, which is worthy of futuristic experimentation.